Effect of the photoactivation method on composite resin cure. - Abe, Andrea Tami (2015)
For composite resins to obtain good properties, they must present a high degree of conversion and minimal polymerization contraction. To minimize this contraction, alternative photoactivation techniques have been suggested. The objective of this study was to compare the hardness of a photoactivated composite resin using the pulse-delay, soft start and continuous conventional technique, in thicknesses of 1, 2 and 3mm. The resin was activated with halogen light and the photoactivation time and intensity varied according to the technique. The samples were stored in an oven at 37ºC for one week and submitted to the Vickers microhardness test, on both the irradiated surface and the opposite surface. The results were submitted to ANOVA and the Tukey’s test with a level of significance of 5%. It was concluded that the hardness was higher with photoactivation of 40 seconds and for the techniques that had the same photoactivation time (20 seconds) there was no difference in terms of hardness. Therefore the hardness is not influenced by the technique, but rather, by the polymerization time.